Oral Provocation Testing in Cutaneous Adverse Drug Reactions to Antiretroviral and Antitubercular Therapy: A Study at a Tertiary Care Hospital in South India - Sowmya Kaimal MBBS, MD; Jithendriya Madhukara MBBS, DVD, DNB (Journal of the International Association of Providers of AIDS Care, 2018)
Aim: To collect data pertaining to oral drug provocation testing (DPT) in hospitalized patients with antiretroviral (ARV)/antitubercular agent–induced rashes. Methods: Patients with cutaneous adverse drug reactions (ADRs) to ARV/antitubercular drugs and who underwent oral DPT during a 5-year period were included in this study. Results: Data were collected from the records of 21 patients. Of the 21, 19 had HIV infection. The most commonly implicated drug was nevirapine (NVP), followed by cotrimoxazole and antitubercular agents. Of the 11 ADRs that occurred on rechallenge, the ADR on rechallenge was similar in clinical presentation to the initial ADR in 6 patients, while a different rash was elicited in 5 patients. Conclusion: Oral DPT is a safe and effective tool to accurately diagnose ADRs, especially in patients on multiple drugs and in situations such as HIV infection and tuberculosis where second-line agents are expensive and/or not easily available through the national AIDS control/tuberculosis programs.